Alfieri come classico nel primo Novecento spagnolo* - Barbolani, Cristina (Cuadernos de Filología Italiana, 2006)
In this article it is considered a Spanish translation of the tragedy Merope by Alfieri, published in the volumen Teatro Clásico Extranjero (1934), Barcelona: HYMSA. In this selection Italy is represented by Goldoni and Alfieri, giving much more relevance to French, English, and German plays. The translator, anonymous, includes both a summary biographical profile of the poet of Asti and brief comments about Alfieri’s theatre peculiarities before his version. Despite his commendable promoted attempt, this version often dilutes the strengh of the conciseness of the original text, misinterprets its darkest passages, and leaves out essential elements arbitrarily. He lacks the rigour and linguistic competence that are necessary to deal with such a substantial translation.